2005
DOI: 10.1093/annonc/mdi247
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of ZD6474, an orally active inhibitor of VEGF and EGF receptor signaling, in patients with solid, malignant tumors

Abstract: Once-daily oral dosing of ZD6474 at 300 mg/day is generally well tolerated in patients with advanced solid tumors, and this dose is being investigated in phase II trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
164
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(177 citation statements)
references
References 20 publications
9
164
2
2
Order By: Relevance
“…Rash and hypertension were also reported as relatively common AEs in a larger phase I study of ZD6474, which was conducted in the United States and Australia. 21 These events could be indicative of target inhibition by ZD6474. Also, because synthesis of the vasodilator nitric oxide is downstream of VEGFinduced angiogenesis signaling, 24 inhibition of VEGFR-dependent signaling by ZD6474 may decrease nitric oxide production and lead to hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rash and hypertension were also reported as relatively common AEs in a larger phase I study of ZD6474, which was conducted in the United States and Australia. 21 These events could be indicative of target inhibition by ZD6474. Also, because synthesis of the vasodilator nitric oxide is downstream of VEGFinduced angiogenesis signaling, 24 inhibition of VEGFR-dependent signaling by ZD6474 may decrease nitric oxide production and lead to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the pharmacokinetic characteristics of ZD6474 in this Japanese study did not differ from those obtained in the U.S./Australian study. 21 Although this study was primarily designed to assess safety and tolerability, secondary assessment of efficacy revealed that four out of nine patients with NSCLC exhibited a partial response to ZD6474 treatment at initial daily doses of 200 mg (n ϭ 3) and 300 mg (n ϭ 1). It is worth noting that partial tumor response was maintained in these patients (range 90 -438 days) despite subsequent reductions in daily dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a substantial dose‐ and exposure‐related QTc prolongation has been observed 79. No clear relationship between PFS and exposure has been found in the pivotal trial in patients with thyroid cancer,79 although multiple studies have used IC 50 values established in vitro (190 ng/mL) to support dose selection in early clinical trials 80…”
Section: Practical Recommendations For Tdm Of Kis In Oncologymentioning
confidence: 99%
“…67 In a phase I trial in 77 patients with various solid carcinomas other than thyroid, doses up to 300 mg daily were tolerated with the most common dose-limiting side effects of diarrhea, hypertension, and skin rash. 68 On the basis of the preclinical demonstration that vandetanib inhibited most RET point mutations, a multicenter, open-label phase II trial studied the efficacy of the drug in patients with metastatic familial forms of MTC. 69 Thirty patients were enrolled, starting therapy with vandetanib, 300 mg daily.…”
Section: Vandetanibmentioning
confidence: 99%